Peran Mahasiswa Magang MBKM dalam Mendukung Layanan Administrasi Divisi Umum Kepegawaian BPPRD Kota Palangka Raya - Alfiatus Sholeha; Haidi Hajar Widagdo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) Program is a policy that provides opportunities for university students to gain direct experience in the professional world. One of its implementations is internships in government institutions. This article is based on a four-month internship undertaken by a student in the General Affairs and Personnel Subdivision of the Regional Tax and Retribution Management Agency (BPPRD) of Palangka Raya City. The aim of this internship is to support office administrative services and to provide students with practical experience in public administration. The methods applied include direct observation, active involvement in administrative tasks, and informal communication with staff members. During the internship, the student participated in various activities such as recording incoming and outgoing mail, typing disposition sheets, scanning and archiving documents, meeting documentation, and distributing files between departments. The results show that student involvement not only helped reduce employees’ workload but also improved the overall efficiency of administrative services. In addition, the student gained a concrete understanding of the bureaucratic system, developed technical skills, and enhanced soft skills relevant to future career readiness. This internship demonstrates that synergy between educational institutions and government agencies can create a meaningful and applicable learning environment for both parties.